2015
DOI: 10.15452/cejnm.2015.06.0025
|View full text |Cite
|
Sign up to set email alerts
|

Self-help group and the quality of life of patients with multiple sclerosis - Pilot study

Abstract: Aim: The goal of the pilot study was to compare the quality of life of patients with multiple sclerosis in the Presov region with or without the support of a self-help group. Design: The character of this pilot study on patients with MS was related to the use of self-help groups and their impact on the assessment of the quality of life of the respondents, with the help of a questionnaire (WHOQOL-BREF). Methods: The research was carried out in the Prešov region with the help of the standardized WHOQOL-BREF ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Eliášová et al 124 found more improvement across several QoL domains in patients with MS after self-help group sessions than in patients who did not attend the self-help groups. Liu 125 detected an increase in physical and psychological QoL in women with MS after participating in a hope-based group therapy programme for 1 hour twice a week for 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eliášová et al 124 found more improvement across several QoL domains in patients with MS after self-help group sessions than in patients who did not attend the self-help groups. Liu 125 detected an increase in physical and psychological QoL in women with MS after participating in a hope-based group therapy programme for 1 hour twice a week for 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…A wide spectrum of interventions based on social support concentrated on reinforcement of the social network of patients with MS, for example, self-help groups, 124 hope-based group therapy, 125 supportive–expressive therapy 121 and social cognitive training with support partners. 122 123 All interventions aimed at helping people overcome MS barriers in daily living by strengthening their social support, improving some aspects of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting pilot study was conducted by Eliášová et al (2015), which aimed to compare the quality of life of patients with sclerosis multiplex in the Presov region in terms of the use of self-help group support. In their paper, they used the same WHOQOL-BREF tool to compare the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, social support perceived from various sources is very important to increase the social desirability of patients and to protect their mental health. According to the study conducted by Eliášová et al, 75 MS patients emphasize that they can lead a normal life as long as they are supported by their families, friends and society 75 . In our study, the total social support score perceived from family, friends and a significant other was 54.93 ( SD : 14.91), and it was observed that the group receiving the most support was from family (22.06 ± 4.64).…”
Section: Discussionmentioning
confidence: 99%